Estudo da utilização de indicadores de desempenho para avaliação da qualidade dos serviços de esgotamento sanitário - Tiago Lages Von Sperling (2010)
This research developed a comparative study of the use of performance indicators in sewerage services by various agencies involved with sanitation, with the aim of proposing a single set The national organizations studied were: Sistema Nacional de Informações sobre Saneamento (SNIS), Associação Brasileira de Agências de Regulação (ABAR) and Prêmio Nacional de Qualidade do Saneamento (PNQS). Globally it were studied the International Water Association (IWA), Instituto de Regulação de Águas e Resíduos de Portugal (IRAR), the Associación de Entes Reguladores de Agua Potable e Saneamiento de las Americas(ADERASA), the International Benchmarking Network for Water and Sanitation Utilities (IBNET), the Six-Cities Group in Scandinavia, the Water Services Association of Australia (WSAA), American Water Works Association (AWWA) and the Office of Water Services (OFWAT).From among the eleven organizations studied, 699 performance indicators were collected, with 483 of them related to sewage services, focus of this work. The indicators were classified into five dimensions proposed (human resources, infrastructure, operational, quality andeconomic-financial), yielding a total of 256 indicators. They were pre-selected and 174 indicators were sent to 107 sanitation experts in order to define the importance and practicality of the indicators and the relevance for the four actors involved in sanitation services: operators, regulators, governments and users. It was proposed 46 performance indicators from the base guiding the study. Results showed aclear predominance of economic and financial indicators. With regard to the actors and relevance for sanitation sector, all proposed indicators were considered relevant to the operators, 42 of them relevant to the regulatory agencies, 38 to government and 7 to users.